Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1155/2012/147031
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Isolation and HPLC Determination of Bioactive Compound That Relate to the Antiplatelet Activity (Adhesion, Secretion, and Aggregation) fromSolanum lycopersicum

Abstract: In seeking the functionality of foodstuff applicable to medicine, ripe tomato fruits were found to show an antiplatelet activity. Therefore, the bioactive compound was isolated, structurally identified, and studied for an inhibitory effects on platelet adhesion, secretion, and aggregation. The concentration of adenosine in ripe tomato fruits (pulp and skin extracts) and its processing by-products (paste and pomace) was determined by reversed-phase high-performance liquid chromatography (HPLC). According to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…In summary, these results demonstrating the actions of tAF on different platelet functions were all consistent with potential effects mediated partly through polyphenols and PDI and partly through nucleosides elevating cAMP and cGMP levels in platelets [13, 67]. Effects on TF binding suggested that tAF components could have a larger effect on some aspects of the coagulatory response, such as thrombin generation, than previously imagined.…”
Section: In Vitro Studies With Water-soluble Tomato Extract On Human supporting
confidence: 78%
“…In summary, these results demonstrating the actions of tAF on different platelet functions were all consistent with potential effects mediated partly through polyphenols and PDI and partly through nucleosides elevating cAMP and cGMP levels in platelets [13, 67]. Effects on TF binding suggested that tAF components could have a larger effect on some aspects of the coagulatory response, such as thrombin generation, than previously imagined.…”
Section: In Vitro Studies With Water-soluble Tomato Extract On Human supporting
confidence: 78%
“…In addition, our group recently isolated and identified adenosine and guanosine from S. lycopersicum. Adenosine and guanosine at a low concentration showed potent antiplatelet activity through the inhibition of platelet secretion, adhesion, and aggregation [15,41]. In the present study, we extended these observations by exploring the antiplatelet effects of extracts and fractions from C. digitatus.…”
Section: Effects Of C Digitatus Extracts and Fractions On Platelet Amentioning
confidence: 60%
“…Because we have recently demonstrated that the aqueous fraction from S. lycopersicum contains significant amounts of adenosine [20], we hypothesized that the antiplatelet effect could be exerted by rising cAMP levels. At 1 mg/mL the aqueous fraction significantly increased the intraplatelet levels of cAMP from 3.5 ± 1 to 20 ± 2 pmol/10 8 platelets ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Total extract and aqueous fraction from Solanum lycopersicum were obtained according to Fuentes et al [20]. Briefly, the total extract was fractionated by liquid-liquid separation, obtaining an aqueous, ethyl acetate, and petroleum ether fractions.…”
Section: Methodsmentioning
confidence: 99%